2019
DOI: 10.1155/2019/6490161
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation of Ulna and Radius in Forearm Radiographs

Abstract: Automatic segmentation of ulna and radius (UR) in forearm radiographs is a necessary step for single X-ray absorptiometry bone mineral density measurement and diagnosis of osteoporosis. Accurate and robust segmentation of UR is difficult, given the variation in forearms between patients and the nonuniformity intensity in forearm radiographs. In this work, we proposed a practical automatic UR segmentation method through the dynamic programming (DP) algorithm to trace UR contours. Four seed points along four UR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Faisal et al found that the range of Dice coefficients for the segmentation of eight carpal bones was 0.83~0.94 when the locally weighted K-means variational level set was applied, whereas the range was 0.91~0.96 when Fine Mask R-CNN was employed in our study [ 22 ]. Goo et al showed that the mean Dice coefficient of the automatic segmentation of the distal ulna and radius with dynamic programing was about 0.90, when using forearm radiographs [ 17 ], while we achieved a mean [SD] Dice of 0.96 (0.01) with Fine Mask R-CNN. The use of a fracture detection CNN without segmentation, based on a Dense-161, for distal radio-ulnar fractures on plain radiographs showed a sensitivity of 90.3%, with a specificity of 90.3% [ 38 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Faisal et al found that the range of Dice coefficients for the segmentation of eight carpal bones was 0.83~0.94 when the locally weighted K-means variational level set was applied, whereas the range was 0.91~0.96 when Fine Mask R-CNN was employed in our study [ 22 ]. Goo et al showed that the mean Dice coefficient of the automatic segmentation of the distal ulna and radius with dynamic programing was about 0.90, when using forearm radiographs [ 17 ], while we achieved a mean [SD] Dice of 0.96 (0.01) with Fine Mask R-CNN. The use of a fracture detection CNN without segmentation, based on a Dense-161, for distal radio-ulnar fractures on plain radiographs showed a sensitivity of 90.3%, with a specificity of 90.3% [ 38 ].…”
Section: Discussionmentioning
confidence: 76%
“…However, most wrist bone segmentation methods use conventional mathematical methods. Gou et al conducted automatic segmentation through a dynamic programming algorithm [ 17 ], and Manos et al employed the region growing [ 18 ] and region merging algorithms sequentially after pre-processing, using a Canny edge detector [ 19 ]. In addition, some advanced algorithms have been applied to overcome the disadvantages related to each medical image domain by combining these conventional methods [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The local entropy method was developed for the detection and segmentation of the radius and ulna bones [ 20 ]. Furthermore, the dynamic programming algorithm was applied to segment the ulna and radius for single-energy X-ray absorptiometry BMD measurement [ 21 ]. However, those methods are easily affected by noise.…”
Section: Introductionmentioning
confidence: 99%